2015
DOI: 10.2196/publichealth.4777
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Marketing Online: a Multi-Site, Multi-Product Comparison

Abstract: BackgroundElectronic cigarette awareness and use has been increasing rapidly. E-cigarette brands have utilized social networking sites to promote their products, as the growth of the e-cigarette industry has paralleled that of Web 2.0. These online platforms are cost-effective and have unique technological features and user demographics that can be attractive for selective marketing. The popularity of multiple sites also poses a risk of exposure to social networks where e-cigarette brands might not have a pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Social media platforms such as Facebook, Twitter, and Instagram are common places to find advertisements, information, and content on e-cigarettes (Chu, Sidhu, & Valente, 2015; Kim et al, 2015; Link, Cawkwell, Shelley, & Sherman, 2015; Luo, Zheng, Zeng, & Leischow, 2014). Nearly 90% of young adults use at least one social media platform (Perrin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Social media platforms such as Facebook, Twitter, and Instagram are common places to find advertisements, information, and content on e-cigarettes (Chu, Sidhu, & Valente, 2015; Kim et al, 2015; Link, Cawkwell, Shelley, & Sherman, 2015; Luo, Zheng, Zeng, & Leischow, 2014). Nearly 90% of young adults use at least one social media platform (Perrin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has consistently found that individuals are exposed to, search for, and share information about e-cigarettes on social media platforms like Twitter and Facebook, among others [14-17]. Interestingly, e-cigarette users are “more likely to be exposed to e-cigarette information via TV viewing sites (eg, Hulu), Twitter, Facebook, email, and Internet search engines” than nonusers [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Baumann et al 21 observed that among hospitalised smokers, 13% of whites vs 6% of blacks had been exposed to online ENDS advertising. Other research indicates that ENDS companies have not been targeting racial/ethnic minority groups via online social networks 22. For example, Chu et al observed no difference in ENDS advertising on websites appealing to blacks during Black History Month 2…”
Section: Discussionmentioning
confidence: 99%
“…The internet has been a particularly attractive advertising medium to ENDS vendors due to its low cost, unique technological features and precise segmentation of the target audience 2. The low cost is especially attractive to small vendors who have tremendous potential for expanding their marketing base.…”
Section: Introductionmentioning
confidence: 99%